Plasma sputtering depositions with colloidal masks for fabrication of nanostructured surfaces with enhanced photocatalytic activity. (30th May 2017) - Demeter, Alexandra; Tiron, Vasile; Lupu, Nicoleta; Stoian, George; Sirghi, Lucel
Abstract: Titanium oxide/silicon oxide (TiO2 /SiO2 ) 2D patterns were obtained by magnetron sputtering depositions of Ti on close-packed and size-reduced colloidal masks on Si and quartz substrates, followed by mask lift-off and ending with thermal oxidation. The physical processes involved in growing 2D Ti patterns and their oxidation are analyzed. For the magnetron sputtering deposition, two regimes are considered: the low-pressure regime when the flux of sputtered atoms is anisotropic, and the high-pressure regime, when the flux of sputtered atoms is isotropic due to frequent collisions. Moreover, magnetron sputtering operation modes, such as dc sputtering and high power impulse sputtering, are compared. The changes in pattern size and morphology determined by the oxidation of the Ti patterns and Si substrate are analyzed. The hydrophilicity induced by UV-light irradiation and the visible-light photocatalytic activity towards the degradation of the methylene blue of the fabricated TiO2 /SiO2 patterns were considerably higher when compared to the performances of uniform TiO2 films.